Delphi consensus recommendation for optimization of pulmonary hypertension therapy focusing on switching from a phosphodiesterase 5 inhibitor to riociguat. (7th April 2022) - Rahaghi, Franck F.; Balasubramanian, Vijay P.; Bourge, Robert C.; Burger, Charles D.; Chakinala, Murali M.; Eggert, Michael S.; Elwing, Jean M.; Feldman, Jeremy; King, Christopher; Klinger, James R.; Mathai, Stephen C.; McConnell, John Wesley; et al.
Abstract: Dual combination therapy with a phosphodiesterase‐5 inhibitor (PDE5i) and endothelin receptor antagonist is recommended for most patients with intermediate‐risk pulmonary arterial hypertension (PAH). The RESPITE and REPLACE studies suggest that switching from a PDE5i to a soluble guanylate cyclase (sGC) activator may provide clinical improvement in this situation. The optimal approach to escalation or transition of therapy in this or other scenarios is not well defined. We developed an expert consensus statement on the transition to sGC and other treatment escalations and transitions in PAH using a modified Delphi process. The Delphi process used a panel of 20 physicians with expertise in PAH. Panelists answered three questionnaires on the management of treatment escalations and transitions in PAH. The initial questionnaire included open‐ended questions. Later questionnaires consolidated the responses into statements that panelists rated on a Likert scale from −5 ( strongly disagree ) to +5 ( strongly agree ) to determine consensus. The Delphi process produced several consensus recommendations. Escalation should be considered for patients who are at high risk or not achieving treatment goals, by adding an agent from a new class, switching from oral to parenteral prostacyclins, or increasing the dose. Switching to a new class or within a class should be considered if tolerability or other considerations unrelated to efficacy are affecting adherence. Switching from a PDE5i to an SGC activator may benefit patients with intermediate risk who are not improving on their present therapy. These consensus‐based recommendations may be helpful to clinicians and beneficial for patients when evidence‐based guidance is unavailable.